Causal relationship between service guarantees and customer satisfaction in four-and five-star hotels in Malaysia - Mohd Shahril, Aslinda (2014)
One of the main issues in the hotel sector, particularly in the four-and five-star hotel in Malaysia, is the inability to implement full service guarantees since employee cannot deliver the service promise. The four-and five star hotels continuing difficulty in delivering reliable, high-quality service to customers. As a result, it decreased customer satisfaction. Additionally, studies showed that empowerment has also become issues in Malaysian hotel. Due to lack of empowerment, employee motivation and job satisfaction was reported low. On the other hand, in the context of service guarantees, service recovery was inefficient due to lack of employee skill to deal with customers. Consequently, a lack of empowerment and employee participation will affect the hotel service performance and the service guarantees offered by the hotel. The purpose of the study are to examine the relationship between service guarantees, service quality, empowerment, employee motivation, job satisfaction, service recovery and customer satisfaction in four-and five-star hotels in Malaysia and the study treats empowerment as a mediating variable. This study is based on the positivism paradigm and employs a quantitative method. The study chose a survey design with questionnaires distributed to front-line employees and hotel customers. It was a self-completion questionnaire for employees; however, the researcher assisted customers when they filling the questionnaire should any ambiguous questions aroused. The structural equation modeling (SEM) analysis results suggested that half of the proposed hypotheses were supported for the employee study, whereas four out of six hypotheses were supported in the customer study. The study found a positive relationship between service guarantees and service quality in the customer study and that service guarantees assist customers in differentiating between sellers of high-and low-quality services. On the other hand, it was found that empowerment play a significant role in service guarantees and contributes to employee participation. The results of this study add support to the signaling theory that service guarantees act as quality signal to customers and a marketing tool that conveys an impression of quality service. Additionally, it provides support for total quality management (TQM) theory, which states that empowerment encourages employee participation, leading to service improvements. This study highlights the importance of service guarantees in delivering and managing quality service in the hotel sector and notes that employee participation is crucial to maintaining the reputation of a business. Finally, service guarantees increase customers‟ purchase intention and facilitate their selection of quality hotels.